El Excentrico, 1965-01-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
January 5, 1965 [5 de enero de 1965]. Ano 15, No 6.. Cover has a photograph of a Yvonne reading a story to her child, Rebecca Kim Cook. The headline reads, "Rebecca Kim Cook gets Christmas briefing from mother Yvonne."